The effect of pharmaceutical composition based on L-carnitine on structural and functional features of rat placenta in the model of passive tobacco smoking - I.V. Volokhov; V.A. Rybak; L.Yu. Sergienko; S.S. Sokolova; S.P. Kustova (Medičnì Perspektivi)
Passive tobacco smoking in modern society is quite common phenomenon. Maternal smoking, including passive smoking, is one of the modifying risk factors for adverse pregnancy outcomes and is associated with disorders of the pregnant woman's reproductive system, including the development of placental dysfunction. The aim of this study was to investigate the effect of a pharmaceutical composition based on L-carnitine on the structural and functional features of the rat placenta in a model of passive tobacco smoking. The study was conducted on 40 nonlinear pregnant rats aged 6 months. Passive smoking modeling was performed from day 1 to day 20 of pregnancy. From the first day of gestation, daily for 20 days, rats were intragastrically administered a pharmaceutical composition based on L-carnitine at an effective dose of 25 mg/kg, and rats of the positive control group received the reference drug at a dose of 68 mg/kg. On the 20th day of pregnancy, the animals were withdrawn from the experiment to study the microstructure of the placenta and determine the level of sex hormones. Structural and functional changes in the rat placenta in the model of passive tobacco smoking were determined. The gravidoprotective effect of the pharmaceutical composition based on L-carnitine at a dose of 25 mg/kg in pregnant rats with a reproduced model of passive smoking was proved, which was manifested by a decrease in histomorphological and hormonal signs of fetoplacental insufficiency compared to the negative control. The gravidoprotective effect in rats treated with a pharmaceutical composition based on L-carnitine and exposed to passive smoking was manifested by a significant decrease in the severity of negative changes in the placental histological structure, which were recorded in animals from the passive smoking group, as evidenced by the following signs of increased width of the labyrinthine section normal width of the decidual membrane, no expansion of blood-filled lacunae, sufficient contact area of fetal and maternal vessels, no signs of thrombosis in maternal lacunae, the predominant number of fetal capillaries without signs of hemostasis with normal blood filling and wall thickness. The use of a pharmaceutical composition based on L-carnitine at a dose of 25 mg/kg in pregnant rats with a reproduced model of passive smoking reduces the damaging effect of cigarette combustion products on placental steroidogenesis. This is manifested by a less pronounced decrease in progesterone levels by 22.47% and free estriol by 55.48% compared to animals exposed to passive smoking, which almost corresponds to the activity of the reference drug at a dose of 68 mg/kg. The presence of a gravidoprotective effect of the pharmaceutical composition based on L-carnitine indicates the prospects for further pharmacological studies to prevent and treat the negative effects of fetoplacental insufficiency on the mother and fetus caused by placental hypoxia due to tobacco smoking.